PUTUSAN MAJELIS KEHORMATAN DISIPLIN KEDOKTERAN INDONESIA SEBAGAI ALAT BUKTI DALAM HUKUM ACARA PIDANA - I Komang Gede Oka Wijaya (Yuridika, 2017)
Evidentiry of the existence of the alleged medical negligence, who is performed by a doctor is very difficult to do, provisions of law of general application, both in civil law (Burgerlijk Wetboek), criminal law and criminal procedure law can not necessarily be applied to cases in which one side is the doctor as medical personnel. After the enactment of Act No. 29 Year 2004 concerning Medical Practice, there is an institution which authorized to determine the presence of errors in the application of medical disciplines performed by a doctor. In the Indonesian Medical Council Regulation No. 32 Year 2015 Article 62 paragraph 2 implicitly mentioning the MKDKI Decision can not to use as evidence in determining medical negligence actions performed by a doctor. This is not accordance with the Constitutional Court Decision No. 14/ PUU-XII/ 2014 and the Criminal Procedure Code.